PELATIHAN MEMBUAT SABUN MANDI ANTI BAKTERI ALAMI DARI DAUN MIMBA (Azadirachta indica A.Juss) DI DESA PENARUKAN KERAMBITAN TABANAN - Santi, Sri Rahayu; Sukadana, I M,; Bogoriani, W. (Buletin Udayana Mengabdi; Vol 10 No 2 (2011): Volume 10 No.2 – September 2011, 2012)
The activity of the community service about the manner of making nature antibacterial soap from Neem leaf (Azadirachta indica A Juss) was conducted on the 24st of October 2010 to the PKK members of Penarukan village, Kerambitan subdistrict, Tabanan Regency. Making nature antibacterial soap has very simple formulaic techniquee. The soap was made by using many chemicals, among others : coconut oil, 32% sodium hydroxide, dextrin, surfactant, dyes, parfume, as well as antibacterial agent from Nemm leaf (Azadirachta indica A Juss). The result of this activity and evaluation showed that the antimicrobial soap product is as good as ordinary soap, having full of foam, not hot without iritation, because it is properly laboratory tested. All of participants showed their enthusiasm during activity and they will try to make soap. This was showed by the evaluation report saying that all participants understand about making soap and they want to try at home. This public service made people interested to improve their knowledge, skill, and possibility to open of new entrepreneur in village so that it can be vacancy and increase income to community.